2009
DOI: 10.1159/000247602
|View full text |Cite
|
Sign up to set email alerts
|

Indices of Kidney Dysfunction and Discharge Outcomes in Hospitalized Stroke Patients without Known Renal Disease

Abstract: Background: The utility of clinical measurements of impairments in glomerular barrier or filtration rate among hospitalized stroke patients without known chronic kidney disease (CKD) has not been well studied. We determined whether various indices of CKD would predict discharge outcomes in persons hospitalized with a recent ischemic stroke. Methods: Presence of proteinuria and estimated low glomerular filtration rate (GFR) <60 ml/min per 1.73 m2 on admission were assessed in consecutive ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
4
43
1
1
Order By: Relevance
“…Stroke patients with CKD had worse functional outcomes than without CKD [2] . However, there are significant discrepancies be- tween our study results and some previous findings showing no association between CKD and functional outcome using the mRS during hospitalization [20,21] . Probably, the variation can be originated from the different measurements and follow-up duration.…”
Section: Discussioncontrasting
confidence: 99%
“…Stroke patients with CKD had worse functional outcomes than without CKD [2] . However, there are significant discrepancies be- tween our study results and some previous findings showing no association between CKD and functional outcome using the mRS during hospitalization [20,21] . Probably, the variation can be originated from the different measurements and follow-up duration.…”
Section: Discussioncontrasting
confidence: 99%
“…11,12,17,21, 22 The difference in study results may be attributed to variations in patient population, sample size and adjusted confounders. BUN is generally considered as being a less specific marker of kidney function than serum Cr and eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research also found that proteinuria, but not low eGFR, was associated with neurological deterioration or a poor functional prognosis after ischemic stroke. 14,15 Thus, there may be a discrepancy between the effects of proteinuria and low eGFR on the shortterm prognosis for ischemic stroke. …”
Section: Discussionmentioning
confidence: 99%